Experimental candidosis and recovery of Candida albicans from the oral cavity of ovariectomized rats - Junqueira, Juliana Campos [UNESP]; Colombo, Carlos Eduardo Dias [UNESP]; Da Silva Martins, Joyce [UNESP]; Ito, Cristiane Yumi Koga [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Wiley, 2005)
The aim of this study was to analyze the development of candidosis and the recovery of C. albicans from the oral cavity of ovariectomized and sham-ovariectomized rats. One hundred aiid twenty-four rats originally negative for Candida spp. in the oral cavity were divided into two groups: ovariectomized and sham-ovariectomized. Fifty-eight ovariectomized and the same quantity of sham-ovariectomized rats were inoculated with C. albicans for the study of candidosis development and recovery of yeast. Four animals from each group were not inoculated with yeast suspension and were submitted to tongue dorsum morphologic analysis by optical and scanning electron microscopy. The development of candidosis in the tongue dorsum was observed by optical and scanning electron microscopy in the periods of 6 hr, 24 hr, 7 days and 15 days after the last inoculation. Recovery of C. albicans was performed by oral samples plating on Sabouraud agar after 1,2, 5 and 7 days and progressively at each 15-day interval until negative cultures for yeasts were obtained. The results were analyzed by Mann-Whitney and Student's t tests. The tongue dorsum of sham-ovariectomized and ovariectomized rats, not infected by Candida, presented normal aspect. Among the infected rats, the ovariectomized group showed less occurrence of candidosis lesions and lower recovery of C. albicans from the oral cavity in relation to the sham-ovariectomized group. It could be concluded that candidosis was less frequent from the oral cavities of ovariectomized rats in relation to sham-ovariectomized.
Keywords: Candida albicans; Oral candidiasis; Ovariectomy; Rat; animal model; animal tissue; candidiasis; controlled study; female; fungus culture; microscopy; mouth cavity; mycosis; nonhuman; ovariectomy; rat; scanning electron microscopy; thrush; tongue; yeast; Animals; Candidiasis, Oral; Disease Models, Animal; Estradiol; Female; Microscopy, Electron, Scanning; Mouth Mucosa; Progesterone; Rats; Rats, Wistar; Tongue